2004
DOI: 10.1177/021849230401200208
|View full text |Cite
|
Sign up to set email alerts
|

Dose Comparison of Tranexamic Acid in Pediatric Cardiac Surgery

Abstract: To compare different doses of tranexamic acid, 150 consecutive children with congenital cyanotic heart disease were randomly assigned to one of 5 groups of 30 each. Group A served as a control. Group B received 50 mg.kg(-1) of tranexamic acid at induction of anesthesia. Group C received 10 mg.kg(-1) at induction followed by an infusion of 1 mg.kg(-1).h(-1). Group D had 10 mg.kg(-1) at induction, 10 mg.kg(-1) on bypass, and 10 mg.kg(-1) after protamine. Group E had 20 mg.kg(-1) at induction and again after prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 16 publications
8
79
0
3
Order By: Relevance
“…For pediatric cardiac surgery, Schouten et al 25 reported that TXA reduced PRBC transfusion by 7 ml/kg (95% CI, 10 -5 ml/kg) compared with the placebo group. These results are similar to those of others studies 18 for the same type of surgery. In young children, we report that TXA reduced the mean PRBC transfusion volume by 9.4 ml/kg during the study compared with a placebo group receiving saline.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For pediatric cardiac surgery, Schouten et al 25 reported that TXA reduced PRBC transfusion by 7 ml/kg (95% CI, 10 -5 ml/kg) compared with the placebo group. These results are similar to those of others studies 18 for the same type of surgery. In young children, we report that TXA reduced the mean PRBC transfusion volume by 9.4 ml/kg during the study compared with a placebo group receiving saline.…”
Section: Discussionsupporting
confidence: 93%
“…They stated a nonsignificant trend of blood transfusion requirement decrease in the treated group compared with the placebo group during surgery and the postoperative period. 23 A few studies 13,16,17,20,23 have shown that intraoperative TXA administration led to less blood loss compared with a placebo group for different types of surgery. Nevertheless, some researchers 19,22 did not report a significant difference in blood loss using TXA or aprotinin, despite a significant decrease in total blood transfusion in the treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been 11 comparative studies of lysine analogs in pediatric patients totaling >1000 patients. 147,[445][446][447][448][449][450][451][452][453][454][455] These are well described in a recent review and meta-analysis, and Table 7 summarizes the results of these studies. 445,456 These studies are of varying quality, and more than half of the patients have come from a single institution, the All-India Institute of Medical Sciences.…”
Section: Prevention and Treatment Of Postoperative Coagulopathymentioning
confidence: 99%